DANOS DE Spodoptera frugiperda (J. E. SMITH, 1797) (LEPIDOPTERA: NOCTUIDAE) NA CULTURA DO MILHO (Zea mays L.) - Lourenção, André Luis Faleiros; Santos, Honório Roberto dos (REVISTA DE AGRICULTURA, 2016)
DANOS DE Spodoptera frugiperda (J. E. SMITH, 1797) (LEPIDOPTERA: NOCTUIDAE) NA CULTURA DO MILHO (Zea mays L.)